2020
DOI: 10.1097/inf.0000000000002509
|View full text |Cite
|
Sign up to set email alerts
|

What Matters to Parents Regarding Immunization of Their Children

Abstract: Under the terms of this licence, you may copy, redistribute and adapt the work for non-commercial purposes, provided the work is appropriately cited, as indicated below. In any use of this work, there should be no suggestion that WHO endorses any specific organization, products or services. The use of the WHO logo is not permitted. If you adapt the work, then you must license your work under the same or equivalent Creative Commons licence. If you create a translation of this work, you should add the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Vaccine hesitancy, defined as a delay in the acceptance or refusal of vaccines despite the availability of vaccine services [1,2], has increased over recent years [3][4][5][6] and was recognized as one of the top ten threats to global health in 2019 [7]. A 2019 national survey from the United States (U.S.) found that approximately one out of four parents reported serious concerns towards vaccinating their children [8] and parental vaccine hesitancy in regard to their children may hamper efforts to curtail the COVID-19 pandemic [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccine hesitancy, defined as a delay in the acceptance or refusal of vaccines despite the availability of vaccine services [1,2], has increased over recent years [3][4][5][6] and was recognized as one of the top ten threats to global health in 2019 [7]. A 2019 national survey from the United States (U.S.) found that approximately one out of four parents reported serious concerns towards vaccinating their children [8] and parental vaccine hesitancy in regard to their children may hamper efforts to curtail the COVID-19 pandemic [9].…”
Section: Introductionmentioning
confidence: 99%
“…This information can help public heath officers design specific campaigns to enhance vaccine acceptance and improve herd immunity. Previous studies have focused on understanding and addressing individual and community vaccine hesitancy [4][5][6]13]. Concerns about vaccine hesitancy have been further heightened during the COVID-19 pandemic, at a time when reaching herd immunity is essential to public health and mitigation of widespread infection.…”
Section: Introductionmentioning
confidence: 99%
“…A s pediatric infectious disease specialists with a specific interest in vaccines, we often receive requests for consultation from colleagues and lay persons regarding postimmunization measles serologies 1 .…”
mentioning
confidence: 99%